Racial and Economic Factors in Attitudes to Immigration - Christian Dustmann; Ian Preston (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2004)
Economic approaches to the political economy of immigration tend to focuson the effects of immigration within models of labour market competition. Concerns about the welfare system may however be an additional factor to fuel hostility towards immigration if immigrants are considered to be competitors for these resources. Hostility towards immigration may also however have cultural motivations that are unrelated to any economic considerations. We try to separate racial and economic components to attitudes towards immigration empirically using evidence on attitudes in the UK. Our analysis is based on the British Social Attitudes Survey 1983 - 1991, which includes questiosn on attitudes towards immigration from a number of different minority groups, as well as attitudes towards related concerns, like job security, benefit expenditures and racial tolerance. Based on this unusually rich data source, we relate expressed opinions on immigration policy to responses regarding these related concerns. Our results point to association of hostility to immigration with concerns in all of these three dimensions but it is expressions of racial intolerance which are most strongly connected to hostility to immigration, particularly where immigration is from countries with predominantly nonwhite populations. We separate our samples according to education and skills and find that the dominant role for racial concerns emerges most strongly for less educated and lower skilled sections of the population for whom we can find no strong evidence for the hypothesis that labour market concerns lead to opposition towards further immigration.
Keywords: 330